Investments on climate-smart agriculture have reached USD5.4 million in Latin America supported by CCAFS science. - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
Through the CCAFS approach on closing gaps between research and action across levels on climate-smart agriculture (CSA), local and subnational partners in Colombia and Guatemala were able to leverage USD5.8 million through both national and international funding sources. The research on CSA and Digital CSA enabled these stakeholders to implement subnational climate change strategies that are aligned with national policies, as well as, to make more robust interventions addressing productivity, adaptation, and mitigation to climate change while improving rural livelihoods.